Revolution with a human face : politics, culture, and community in Czechoslovakia, 1989-1992 - Krapfl, James, 1971- (Cornell University Press, 2013)
As a history of Czechoslovakia's "gentle revolution," this book shifts the focus away from elites to ordinary citizens who endeavored - from the outbreak of revolution in 1989 to the demise of the Czechoslovak federation in 1992 - to establish a new, democratic political culture. Unique in its balanced coverage of developments in both Czech and Slovak lands, including the Hungarian minority of southern Slovakia, this book looks beyond Prague and Bratislava to collective action in small towns, provincial factories, and collective farms